ANALISIS KETERAMPILAN TEKNIK DASAR BOLA VOLI CLUB BOLA VOLI PUTRA METEOR DERMOLO JEPARA - Ramara, Alunnuarta Dias; Sistiasih, Vera Septi; Jariono, Gatot; Nugroho, Hanif (Jurnal Porkes, 2025)
This study aims to evaluate the level of basic technical skills of upper serve, upper pass, and smash in male players of Club Meteor Dermolo. This study used a quantitative approach with a survey method, involving 32 players as a population with 15 male players selected as samples through purposive sampling technique. Data collection was done through skill tests, including upper serve, smash, and upper pass tests. Data analysis used descriptive statistics as well as direct observation to provide a comprehensive picture of the players' abilities. The results showed that the upper serve and smash skills of most players were in the good category, while the upper pass had considerable variation, with an average score of 51.86 and a standard deviation of 6.57.  The average (mean) of all test results is 40.13, with a standard deviation of 1.72. The mean of all test results was 23.33, with a standard deviation of 0.816. The mean value of the overall test results was recorded at 51.86 with a standard deviation of 6.57. These findings indicate the need for a more structured training program that focuses on improving upper passes to create a balance of basic technical skills among players, thereby improving overall team performance.